2016
DOI: 10.1371/journal.pone.0154733
|View full text |Cite
|
Sign up to set email alerts
|

What Difference Does a Visit Make? Changes in Animal Welfare Perceptions after Interested Citizens Tour a Dairy Farm

Abstract: Citizens’ concerns about farm animal welfare are often dismissed on the assumption that they are not well informed about farming practices. We conducted exploratory surveys of interested citizens (n = 50) before and after a self-guided tour of a 500-head dairy farm. ‘Before’ survey questions explored perceptions, concerns, and values about dairy cattle farming and welfare, in addition to a short knowledge-based quiz on dairy cattle husbandry. An ‘after’ survey explored the extent to which these constructs shif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
122
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(131 citation statements)
references
References 35 publications
8
122
0
1
Order By: Relevance
“…In another relevant study, Ventura et al (2016a) examined the views of individuals with little previous exposure to dairy, before and after they toured a working dairy farm. Visiting this farm seemed to address certain concerns, including that cows did not have adequate access to food and water and that they were not handled appropriately.…”
Section: Educate the Publicmentioning
confidence: 99%
See 3 more Smart Citations
“…In another relevant study, Ventura et al (2016a) examined the views of individuals with little previous exposure to dairy, before and after they toured a working dairy farm. Visiting this farm seemed to address certain concerns, including that cows did not have adequate access to food and water and that they were not handled appropriately.…”
Section: Educate the Publicmentioning
confidence: 99%
“…Moreover, there is also some evidence suggesting that moral values appear to have a greater impact on negative attitudes towards farm-animal welfare than does factual knowledge (Boogaard et al 2011), which may explain why criticisms regarding production practices fail to disappear following an educational intervention. As Ventura et al (2016a) concluded (p. 15), 'livestock industries cannot expect one-way education efforts (even immersive experiences such as a farm tour) to resolve societal concerns about animal welfare'.…”
Section: Educate the Publicmentioning
confidence: 99%
See 2 more Smart Citations
“…Pastures are preferential to other animal feed resources, as having high nutritional value, and good taste, meeting nutritional requirements of herbivorous (cattle, sheep, goats, horses, etc.). Animals that feed on pastures have better health because they are daytime in the fresh air and other influence in health [10,11]. Therefore, this also has an impact on the productivity and fertility of animals, are cheaper meals and there is no need to invest in food preparation, Plots in which grazing is continuously improved has an impact on the grazing quality.…”
Section: Importance Of Forage and Pastures In Kosovomentioning
confidence: 99%